1986
DOI: 10.1002/jmv.1890190308
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune response in hereditary and overt diabetes mellitus

Abstract: The inbred diabetic mutant mouse, C57BL/KsJ db +/db + (db +/db +), spontaneously develops diabetes mellitus when allowed food ad libitum. However, restriction of food intake prevents the expression of this genetic predisposition for diabetes. This experimental design has been used previously to demonstrate a deficient neutralizing antibody response to coxsackievirus B4 (CB4) in mutants with the genetic predisposition only. These observations demonstrate that in the genetically predisposed diabetic mutant, defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
9
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
5
9
0
Order By: Relevance
“…Notwithstanding these strain differences, the capacity of Coxsackie B4 virus to induce diabetes appears to be definitely influenced by the genetic background of the host. Genetic studies showed that the 'db' diabetic mutation on chromosome 4 exerted the most effect on susceptibility and host response to Coxsackie B4 virus [204,205] and was associated with an impaired humoral response to Coxsackie B4 viral infection as infected mice did not develop an adequate level of anti-Coxsackie B4 IgM and IgG antibodies [206,207]. The animals were also found to be deficient in absolute and relative numbers of splenic lymphocyte subsets [208].…”
Section: Coxsackie B Viruses and Animal T1dmentioning
confidence: 95%
“…Notwithstanding these strain differences, the capacity of Coxsackie B4 virus to induce diabetes appears to be definitely influenced by the genetic background of the host. Genetic studies showed that the 'db' diabetic mutation on chromosome 4 exerted the most effect on susceptibility and host response to Coxsackie B4 virus [204,205] and was associated with an impaired humoral response to Coxsackie B4 viral infection as infected mice did not develop an adequate level of anti-Coxsackie B4 IgM and IgG antibodies [206,207]. The animals were also found to be deficient in absolute and relative numbers of splenic lymphocyte subsets [208].…”
Section: Coxsackie B Viruses and Animal T1dmentioning
confidence: 95%
“…Leptin-deficient (ob/ob) mice and leptin receptor-deficient mice (db/db) mice display numerous immune abnormalities (14,15), including CD4 + T cell lymphopenia, increased numbers of natural regulatory T cells, and a resistance to autoimmune disorders including experimental autoimmune encephalomyelitis (EAE), experimental colitis, Ag-induced arthritis, and type 1 diabetes (16).…”
mentioning
confidence: 99%
“…An uncontrolled expansion of autoreactive T cells could favor autoimmunity (20)(21)(22)(23)(24), but in ob/ob mice, CD4 + lymphopenia does not associate with homeostatic proliferation of T cells and autoimmunity (14)(15)(16).…”
mentioning
confidence: 99%
“…Recent experimental evidence (11) supports a direct role for leptin in the regulation of immunity. Leptin-deficient mice (ob/ob), 3 leptin receptor (ObR)-deficient mice (db/db) mice, as well as mice with starvation-induced leptin deficiency, display an array of immune abnormalities (12,13). Administration of leptin reverses the starvation-induced immunosuppression in vivo, and leptin enhances T cell proliferation and Th 1 proinflammatory cytokine production in vitro, conditional on the presence of a functional ObR (14).…”
mentioning
confidence: 99%